2016
DOI: 10.4103/0974-8490.172658
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of chloroform fraction of Cocos nucifera L. husk fiber against Cisplatin-induced toxicity in rats

Abstract: Background:Cisplatin (Cis) is used in the treatment of solid tumors and is known to elicit serious side effects.Objective:The present study investigated the protective effects of chloroform fraction of Cocos nucifera husk fiber (CFCN) against Cis-induced organs’ damage and chromosomal defect in rats. Quercetin (QUE), standard antioxidant, served as positive control.Materials and Methods:Thirty male Wistar rats were assigned into six groups and treated with corn oil (control), Cis alone, Cis + CFCN, CFCN alone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Data from this study showed that extracts from C. nucifera did not only scavenge free radicals but also inhibits peroxidation of lipids in both in vitro and in vivo models. Study also showed that pretreatment of cisplatin‐induced rats with chloroform extracts of C. nucifera husks inhibited lipid peroxidation and enhanced the antioxidant defense system of the experimental animals (Adaramoye, Azeez, & Ola‐Davies, ). Formation of lipid peroxidation byproducts such as malondiadehyde has been linked to reduction in concentration of reduced gluthatione in alloxan‐induced rats as evident in this study as well as other studies (Pari & Umamaheswari, ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from this study showed that extracts from C. nucifera did not only scavenge free radicals but also inhibits peroxidation of lipids in both in vitro and in vivo models. Study also showed that pretreatment of cisplatin‐induced rats with chloroform extracts of C. nucifera husks inhibited lipid peroxidation and enhanced the antioxidant defense system of the experimental animals (Adaramoye, Azeez, & Ola‐Davies, ). Formation of lipid peroxidation byproducts such as malondiadehyde has been linked to reduction in concentration of reduced gluthatione in alloxan‐induced rats as evident in this study as well as other studies (Pari & Umamaheswari, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin was dissolved in saline. Acute renal toxicity was induced by intraperitoneal injection of 10 mg/kg cisplatin, a single dose, at day 5 [ 16 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research, Society and Development, v. 10, n. 10, e426101018994, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i10.18994 nucifera extract, intending to revert toxic effects induced by cisplatin in mice, Adaramoye and Ola-davies (2015) obtained positive results by administrating 200 mg/kg daily on mice diet, they also noticed a decrease in lipid peroxidation and intensification of antioxidant enzymes activity. And finally, the extract obtained from Orbignya phalerata presented a protective effect by modulating the inflammatory response, and the fruit extract from this species associated or not with aluminum particles increased interferons and interleukins concentration (Guerra, Silva, Aragão-frança, Oliveira, & Feitosa, 2011b).…”
Section: Anti-inflammatory and Protective Activitiesmentioning
confidence: 99%